Early events induced by the toxin deoxynivalenol lead to programmed cell death in Nicotiana tabacum cells. (September 2015) - Yekkour, Amine; Tran, Daniel; Arbelet-Bonnin, Delphine; Briand, Joël; Mathieu, Florence; Lebrihi, Ahmed; Errakhi, Rafik; Sabaou, Nasserdine; Bouteau, François
Highlights: Early deoxynivalenol (DON)-induced responses of BY2 cells were explored. DON-induced cell death could require active transcription and translation processes. The cell death is dependent on ion channels regulations leading to cell shrinkage. Mitochondrial dysfunction and H2 O2 production seemed related to this death. Abstract: Deoxynivalenol (DON) is a mycotoxin affecting animals and plants. This toxin synthesized by Fusarium culmorum and Fusarium graminearum is currently believed to play a decisive role in the fungal phytopathogenesis as a virulence factor. Using cultured cells of Nicotiana tabacum BY2, we showed that DON-induced programmed cell death (PCD) could require transcription and translation processes, in contrast to what was observed in animal cells. DON could induce different cross-linked pathways involving (i) reactive oxygen species (ROS) generation linked, at least partly, to a mitochondrial dysfunction and a transcriptional down-regulation of the alternative oxidase ( Aox1 ) gene and (ii) regulation of ion channel activities participating in cell shrinkage, to achieve PCD.